Pemberdayaan Masyarakat Pada Lahan Terbatas Melalui Pelatihan Aquaponik Dengan Budikdamber (Budidaya Ikan Dalam Ember) Di Dukuh Grumbul Sawit Desa Sroyo Kabupaten Karanganyar - Mu'arifuddin, Mu'arifuddin; Yulianto, Yulianto; Alamsyah, M. Ridho; Widyastuti, Aprilia; Cikal Pangestika Nolanda Pisal (Universitas Negeri Semarang, 2024)
Human Empowerment is a starting point for a nation to run well in the future in all walks of life. The concept of community empowerment itself is a development program prioritized by the government. 70% community empowerment has a good impact on reducing poverty in Indonesia. This means that community empowerment can be seen from all sectors that have potential or not. Community empowerment is carried out in the form of raising awareness that it can provide new potential on limited land. The aim of this service is that the UNNES Giat 7 Sroyo Village Team provides alternative solutions to problems related to realizing new potential from limited land. This service is carried out using a comprehensive observation method by carrying out an accompanying methodology to the service location. where the focus is on Kasak Hamlet, Grumbul Sawit Hamlet RT 6 RW 1 and RT 7 RW 1, Sroyo Village, Jaten District, Karanganyar Regency, Central Java Province by means of Aquaponics Training through Budidakmber. The results of the team work program were well received by PKK Grumbul Sawit. and after the Training and Mentoring it can be managed independently by PKK members.